Novel pyrochlores in the Bi2O3–MgO–Ta2O5 (BMT) system: synthesis optimisation, phase equilibria and dielectric properties - Tan, K. B.; Tan, P. Y.; Feng, Y.; Khaw, C. C.; Raman, V.; Murthy, H. C.Ananda; Balachandran, R.; Chen, S. K.; Lee, O. J.; Chan, K. Y.; Zhou, D.; Lu, M. (Elsevier B.V., 2025)
Investigating the phase equilibria within the Bi2O3–MgO–Ta2O5 (BMT) system offers critical insights into the formation and stability of pyrochlore phases. This understanding enables the correlation of dielectric properties with phase equilibria data, facilitating the identification of compositions exhibiting optimal performance. Phase equilibria within the BMT system have been investigated across a temperature range of 800–1025 °C. The layouts of compatible triangles, encompassing two-phase, three-phase regions and the single-phase BMT subsolidus solution area, have been determined through qualitative XRD phase analysis of approximately 150 synthesised compositions. The BMT trapezoidal cubic pyrochlore region could be represented by the general formula of Bi3.56-xMg1.96-yTa2.48+x + yO13.50+x+(3/2)y, 0.00 ≤ x ≤ 0.32; 0.00 ≤ y ≤ 0.20. Two formation mechanisms are proposed: (i) compositions of Bi3.56-xMg1.96Ta2.48+xO13.50+x at fixed MgO content, involving a one-to-one substitution of Bi3+ by Ta5+ and oxygen non-stoichiometry x Bi3+ → x Ta5+ + x O2− and (ii) Bi3.56Mg1.96-yTa2.48+yO13.50+(3/2)y at fixed bismuth content, with Mg content reduction proportional to Ta5+ and O2− substitution, i.e. y Mg2+ → y Ta5+ + 3y/2 O2−. Dielectric properties within this extensive subsolidus solution area exhibit variability; specifically, BMT pyrochlores exhibit dielectric constants (ε′) ranging from 70 to 84, dielectric losses (tan δ) in the order of 0.2–9.1 × 10−3, negative temperature coefficients of dielectric constants (TCε′) ranging from 130 to 360 ppm/°C and activation energies (Ea) ranging from 1.10 to 1.48 eV.